ON THE ORIGIN OF HYDROXYLAPATITE ASSOCIATED WITH PURE MASSIVE MAGNETITE IN THE OTHRYS OPHIOLITE COMPLEX, GREECE - Mitsis, Ioannis; Economou-Eliopoulos, Maria (Ofioliti, 2003)
The Ano Agoriani area of the Othrys ophiolite complex, central Greece, is dominated by plagioclase lherzolites, commonly serpentinized, of likely mantle origin. These rocks are intruded by several irregular bodies and dikes-veins of gabbro, as well as dikes of pyroxenite and pegmatitic gabbro. Small irregular to lens-shaped occurrences of apatite associated with magnetite and/or silicates were discovered along a tectonic contact between the lherzolite and a body of microgabbros. Apatite occurs as euhedral large crystals (up to 3 cm in length) associated with magnetite. The apatite/magnetite modal ratio varies considerably. Apatite may include grains of magnetite, Ni-sulfides and monazite.Apatite is also characterized by the presence of abundant primary fluid inclusions. They are two-phase inclusions, containing an aqueous liquid (L > 50%) and a vapor phase. Stable isotopes of oxygen for apatite and magnetite, and oxygen and hydrogen for fluid inclusions within apatite make been determined. The apatite-magnetite association from the Ano Agoriani area differs from nelsonite hosted by anorthosite suites. The composition of the apatite (hydroxylapatite), the presence of abundant fluid inclusions within apatite, the stable isotope (d18O-dD) data on apatite and the composition of the associated magnetite and sulfides support the hydrothermal origin of the apatite, a significant participation of meteoric water into the hydrothermal system and a relatively low (300oC) temperature during the apatite crystallization.